Management of ventricular arrhythmias in heart failure: Current perspectives - Peichl, Petr; Rafaj, Adam; Kautzner, Josef (Heart rhythm O2, 2021)
Congestive heart failure (HF) is a progressive affliction defined as the inability of the heart to sufficiently maintain blood flow. Ventricular arrhythmias (VAs) are common in patients with HF, and conversely, advanced HF promotes the risk of VAs. Management of VA in HF requires a systematic, multimodality approach that comprises optimization of medical therapy and use of implantable cardioverter-defibrillator and/or device combined with cardiac resynchronization therapy. Catheter ablation is one of the most important strategies with the potential to abolish or decrease the number of recurrences of VA in this population. It can be a curative strategy in arrhythmia-induced cardiomyopathy and may even save lives in cases of an electrical storm. Additionally, modulation of the autonomic nervous system and stereotactic radiotherapy have been introduced as novel methods to control refractory VAs. In patients with end-stage HF and refractory VAs, an institution of the mechanical circulatory support device and cardiac transplant may be considered. This review aims to provide an overview of current evidence regarding management strategies of VAs in HF with an emphasis on interventional treatment.
Keywords: Ventricular arrhythmia; Sudden cardiac death; Catheter ablation; Heart failure; Implantable cardioverter-defibrillator